Using Digital Marketing to Develop Marketing Strategy for Fish Farmer Group Products in Jehem Village - Vidya Shania Devi; Kadek Devi Kalfika Anggria Wardani; Dewa Ayu Putu Adhiya Garini Putri (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Fish Farmer Group "Mina Kumala Sari" is a fish farming group located in Jehem Village, Tembuku District, Bangli Regency and is engaged in fisheries, especially koi fish. Based on observations, it is known that this group still has problems in marketing the product. By using digital marketing through social media, it is hoped that they can reach the target market of the "Mina Kumala Sari" Fish Farmer Group. The purpose of this community service is to find out the use of digital marketing as a marketing strategy for the cultivation of the Fish Farmer Group "Mina Kumala Sari" Jehem Village. The implementation method begins at the observation stage, then conducts interviews with the group leader to gather information, followed by a literature study to collect data from literature and the last stage is documentation in the form of photos and videos. Based on the results of the service, it can be concluded that utilizing social media as a means to market products is quite effective because before the promotion was carried out many people did not know the existence of this group and after promotion through social media and direct and online promotions with groups or communities of ornamental fish lovers caused the Farmers Group Fish "Mina Kumala Sari" is increasingly recognized by the wider community.